ANALISIS KELEMBAGAAN PENGELOLAAN DAERAH PENYANGGA TAMAN NASIONAL KERINCI SEBLAT: STUDI KASUS DI EKS HPH PT MAJU JAYA RAYA TIMBER KABUPATEN BENGKULU UTARA PROVINSI BENGKULU - Khalik, Idham; Kusmana, Cecep; Basuni, Sambas (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2011)
Ex concession of PT Maju Jaya Raya Timber (PT MJRT) is located at North Bengkulu Regency, Bengkulu Province is an important buffer zone of Kerinci Seblat National Park (KSNP). Therefore the damage that happened in that area will have a huge impact in the on-going development of the reservation area. The purpose of this research is to design alternative policies to manage the buffer zone of KSNP. The analytical methods used are the Analytical Hierarchy Process (AHP) and SWOT analysis method are both used to design an alternative policies management. The result of this research showed that there have been changes in land cover, virgin forest only about 30%, and the rest was logged over area and has been converted to field crops owned by the locals and private company. This indicates that the management of ex-concession is not good enough. Based on Analytical Hierarchy Process and SWOT analysis, the prioritize function on the management of the area mentioned has be increasing to income of the locals, therefore this could decrease the pressure of the locals to take advantage in using the forest area. Some alternatives of policies which can be carried out is to strengthen property rights, developed local institution, developed the pattern of agroforestry and to upgrade the human resources by increasing the economic productivity for proper management of KSNP buffer zone. Keywords: Buffer Zone, Ex-Concession, Institution, Land Cover